The Influence Of Intellectual Capital On Firm Value - Nanda Diana; Lili Triana; Mardi Mardi; Itah Miftahul Ulum (Al-Makki Publisher, 2024)
This study aims to analyze the effect of intellectual capital on firm value with Price Book Value (PBV) as the dependent variable, and VACA, VAHU, and STVA as independent variables. The population in this study are public companies listed on the Indonesia Stock Exchange and LQ45. The sampling method used in this study was purposive sampling method, with a total sample of 108 samples. As for analyzing data using multiple regression analysis. Meanwhile, the results of this study indicate that the VACA and VAHU variables have no effect on firm value, while the STVA variable affects firm value. The company will have a competitive advantage if it can codify corporate knowledge and build structural capital. therefore, companies need to consider other strategies for increasing firm value. Thus, this study makes a new contribution by examining the effect of intellectual capital on firm value in companies listed on the Indonesia Stock Exchange and included in the LQ45 index in 2019-2022. This research also provides a new understanding of the relationship between intellectual capital and firm value in the context of public companies in Indonesia.